Integrasi Nilai-Nilai Filsafat Ilmu untuk Penguatan Literasi dan Berpikir Kritis di Kalangan Generasi Z - Daniel Daniel; Muhammad Syukur (Mathematics Education Study Program, 2025)
This research aims to determine the role of philosophical values ​​of science in strengthening the literacy and critical thinking of Generation Z. This qualitative research uses a phenomenological approach. Data was collected through observation, interviews and documentation, and tested for validity using time and content triangulation. The research results show that integrating the values ​​of the philosophy of science can: 1) Strengthen Generation Z literacy through understanding basic concepts of the philosophy of science, improving information analysis skills, and learning evaluation; 2) Improve critical thinking skills through improving test results, reflective-analytic thinking patterns, and rational and structured decision making. Data is analyzed through condensation, presentation and drawing conclusions.